Behavioral and neurological improvement by Cydonia oblonga fruit extract in chronic immobilization stress rats. (17th November 2020) - Sakhri, Fatma Z.; Adachi, Naoki; Zerizer, Sakina; Ohashi, Yusuke; Ikemoto, Hideshi; Tsukada, Mana; Kabouche, Zahia; Hisamitsu, Tadashi; Sunagawa, Masataka
Abstract : It is known that chronic stress is a contributing factor to several physical and mental diseases. In this study, we examined the effect of hydroethanolic extract of Cydonia oblonga fruit (HECO, 300 mg/kg) in chronically immobilized rats on physiological and behavioral parameters by the open field test (OFT), sucrose preference test (SPT), and forced swimming test (FST) and on neurological alterations by analysis of the hippocampal neurogenesis. A daily 6 hr exposure to chronic immobilization stress (CIS) for 21 consecutive days induced anxiety‐ and depressive‐like behaviors in rats' concomitant with decreased weight gain and increased plasma corticosterone (CORT) levels, rats also showed atrophy in the CA3 subregion of the hippocampus and a decreased number of Ki67 and DCX positive cells in the dentate gyrus (DG). Treatment with HECO successfully suppressed the physiological and behavioral markers of the CIS and prevents the structural abnormality and the impaired cell proliferation in the hippocampus. Moreover, the daily administration of HECO improved the mood function in normal rats. Taking together, our findings demonstrate, for the first time, the anti‐depressive effect of C. oblonga fruit by enhancing the hippocampal neurogenesis in the rat model of depression.